Molasses Injection to Improve Growth and Vitality of Kesambi (Schleicera oleosa Merr) as Lac Insect Host Plant - Heri Suryanto; Supriyanto; Noor Farikhah Haneda (Jurnal Penelitian Kehutanan Wallacea, 2018)
Lac is a non-timber forest product derived from the secretion of Laccifer lacca insects that are cultivated in kesambi tree (Schleicera oleosa Merr). Low lac production in Indonesia due to poor conditions of host plant indicated by poor growth symptoms, yellowing, and falling leaves. The aim of this research was to study the effect of molasses injection on the growth and vitality of kesambi tree. Molasses were injected into the plant using passive liquid injection methods. Pre-research activities were carried out by the tree trunk injection in 0.5, 1.5, and 2 meters above the ground using gentian violet to determine the best stem injection position, while the main research activity was performed by injection of the kesambi tree trunk using molasses in concentrations of 5, 10, 15% and water as control. The parameters measured at the pre-study was translocation length of gentian violet whereas at the main research were the volume uptake, the increase of branch diameter growth, total sugar content and chlorophyll content. Pre-research results showed that 1.5 meters above the ground is the best injection position. The main research results indicated that the highest volume uptake was water followed by others treatments. Molasses injection at concentration of 10% gives better effect on the increase of branch diameter growth (4.3 mm), obtained sugar content in 18.46%. The vitality of kesambi tree also increased by the molasses injection at concentration of 10%. It was shown by thein creased of chlorophyll a (1.117 mg/g), b (0.416), carotene (0.365), and Anthocyanin (0.094 mg/100g).